2003
DOI: 10.3201/eid0910.030060
|View full text |Cite
|
Sign up to set email alerts
|

Multijurisdictional Approach to Biosurveillance, Kansas City

Abstract: An electronic reporting system for a network of 22 laboratories was implemented in Kansas City, Missouri, with an independent organization acting as a data clearinghouse between the reporting laboratories and public health departments. The system ran in tandem with conventional reporting methods. Laboratory test orders and results were aggregated and mapped to a common nomenclature. Reports were delivered through a secure Internet connection to the Kansas City Health Department (KCHD); during the first 200 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In Missouri, the Cerner Corporation and the Kansas City Health Department (KCHD) recently collaborated on an electronic reporting system for biosurveillance that takes advantage of a one-to-many messaging architecture and a data-warehousing architecture. 61 A network of 22 laboratories extracted and published new laboratory test orders, results, and patient demographic data on a daily basis to a central data clearinghouse. There the data was loaded into a warehouse, cleansed, and normalized to a common nomenclature.…”
Section: -63mentioning
confidence: 99%
“…In Missouri, the Cerner Corporation and the Kansas City Health Department (KCHD) recently collaborated on an electronic reporting system for biosurveillance that takes advantage of a one-to-many messaging architecture and a data-warehousing architecture. 61 A network of 22 laboratories extracted and published new laboratory test orders, results, and patient demographic data on a daily basis to a central data clearinghouse. There the data was loaded into a warehouse, cleansed, and normalized to a common nomenclature.…”
Section: -63mentioning
confidence: 99%
“…Khan et al (1993Khan et al ( , 1995 demonstrated methods for automatic case finding for hospital infection control, and Jain et al (1996) developed a tuberculosis case detector. Many organizations are creating electronic laboratory reporting systems, which automate case detection by laboratories (Effler et al, 1999;Overhage et al, 2001;Panackal et al, 2001;Hoffman et al, 2003).…”
Section: Case Detection By Computersmentioning
confidence: 99%
“…A definitive tool for biosurveillance is the electronic reporting of diagnostic results confirming the presence of a pathogen. Hoffman et al [53] reported a multijurisdictional approach to biosurveillance using an electronic reporting system that ran in tandem with conventional reporting methods. More reports and more complete reports were received electronically compared with conventional methods.…”
Section: Biosurveillance Electronic Information and Communications mentioning
confidence: 99%